Representation and prediction for locally harmonizable isotropic random fields. (1995) - Swift, Randall J.
Abstract : The class of harmonizable fields is a natural extension of the class of stationary fields. This paper considers fields whose increments are harmonizable and isotropic. Spectral representations are obtained for locally harmonizable isotropic fields. A linear least squares prediction for locally harmonizable isotropic fields is considered.